History of doping violations in Olympic wrestling - Curby, D. (International Journal of Wrestling Science, 2023)
Doping is not new in sport and has ancient origins. From the moment in which individuals began to practice physical activity in competition with others, they have sought to improve their own performance by taking mixtures of various types of plants, mushrooms and meats. The ancient Greek athletes drank wine potions, and used hallucinogens and ate animal hearts or bull or sheep testicles in search of potency. Roman gladiators used stimulants and hallucinogens to prevent fatigue and injury. Gladiators ingested strychnine to stave off fatigue and injury and to improve the intensity of their fights (Mazzeo, Altavilla, D'Elia, & Raiola, 2018). Like many Olympic competitors, Nero drank a potion ot the ashes of wild-boar dung in water, to refresh himself. (Pliny the Elder, The Natural History (Book 28)), (Bowers, 1998).